The Privileged Gaze: Esotericism and Mysticism in Novohispanic Painting - González García, Isabel (2026)
This article analyzes a mystical-themed painting produced in eighteenth-century Puebla by considering the possibility of characterizing its context of production as an esoteric field. The theoretical framework is grounded in the criteria of Western esotericism proposed by Antoine Faivre, in dialogue with William James’s notion of mystical experience and with Victor Stoichita’s studies on visionary imagery. From an art-historical perspective, the study undertakes an iconological–hermeneutic visual analysis focused on representational strategies that articulate gesture, imagination, and symbolic mediation. The article proposes to understand these paintings as sites of convergence between mysticism and esotericism, giving rise to image-documents capable of rendering mystical experience visible, communicable, and socially legible through codes shared by mystics and painters. It concludes that this type of imagery fed back into the cultural and religious horizon of its context of production by functioning as mediating devices between the human and the divin.